1997
DOI: 10.1111/j.1558-5646.1997.tb01467.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Manipulation of Putative Selective Agents Provides Evidence for the Role of Natural Enemies in the Evolution of Plant Defense

Abstract: Although biologists have long assumed that plant resistance characters evolved under selection exerted by such natural enemies as herbivores and pathogens, experimental evidence for this assumption is sparse. We present evidence that natural enemies exert selection on particular plant resistance characters. Specifically, we demonstrate that elimination of natural enemies from an experimental field population of Arabidopsis thaliana alters the pattern of selection on genetic variation in two characters that hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
267
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 352 publications
(272 citation statements)
references
References 75 publications
5
267
0
Order By: Relevance
“…If herbivory is to act as a selective force for plant resistance trait(s), three requirements must be met: (i) there must be phenotypic variability in the plant population in the resistance trait(s); (ii) the trait(s) conferring resistance must be under genetic control; and (iii) the herbivore damage incurred by plants in the absence of the resistance trait(s) must negatively impact the overall fitness of the plant [26,27]. Monoterpenes are typically very variable within conifer populations, including those of Scots pine [28,29].…”
Section: Resultsmentioning
confidence: 99%
“…If herbivory is to act as a selective force for plant resistance trait(s), three requirements must be met: (i) there must be phenotypic variability in the plant population in the resistance trait(s); (ii) the trait(s) conferring resistance must be under genetic control; and (iii) the herbivore damage incurred by plants in the absence of the resistance trait(s) must negatively impact the overall fitness of the plant [26,27]. Monoterpenes are typically very variable within conifer populations, including those of Scots pine [28,29].…”
Section: Resultsmentioning
confidence: 99%
“…Although stem and bud gallers can have clear impacts on plant fitness (Quiring and McKinnon, 1999), the relationship between leaf gallers and plant fitness is not as clear. There are still remarkably few studies that have demonstrated selection by herbivores on specific plant chemical defenses (but see Mauricio and Rausher, 1997;Shonle and Bergelson, 2000). Given the relationship between leaf gallers and alkaloid traits in this study, it would be worthwhile to determine whether leaf gallers have impacts on plant fitness that would translate to selection for defense traits.…”
Section: Discussionmentioning
confidence: 99%
“…Glucosinolates and their breakdown products are genetically variable in Arabidopsis and Brassica, and experience natural selection due to their biological effects on generalist and specialist herbivores (Mauricio and Rausher, 1997;Raybould and Moyes, 2001;Kliebenstein et al, 2002b). High levels of nucleotide polymorphism are maintained by balancing selection at the Arabidopsis GSelong locus (Kroymann and Mitchell-Olds, unpublished), which encodes a glucosinolate biosynthetic enzyme (Kroymann et al, 2001).…”
Section: Patterns Of Genetic Variation At Resistance Locimentioning
confidence: 99%